PERENCANAAN PENGELOLAAN HUTAN RAKYAT DI TANA TORAJA - Daud Malamassam (Forestry Faculty of Universitas Hasanuddin, 2006)
A study on the management planning of Public Forest in Tana Toraja Regency was implemented with the aim of establishing a concept for forest product regulation in order to attain an optimum result and benefits in the interest of the owners and regional development. As the result, the public forest that located on 10 districts in Tana Toraja Regency can be organized into four Management Units. By an appropriate management treatments, every management unit can present an adequate and sustainable quantity of raw material for wood processing industries in this region. Keywords: Management Planning, Public Forest, Yield Sustainability, Management Unit, and Annual Allowable Cut